Zero-contrast transcatheter closure of sinus venosus defect in advanced renal failure - Puthiyedath Thejaswi; Pramod Sagar; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2024)
Transcatheter closure of sinus venosus defect (SVD) is an emerging intervention that utilizes a covered stent to redirect the right upper pulmonary vein to the left atrium. Preprocedural computed tomography analysis, as well as the interventional procedure, necessitates the use of radiographic contrast media. Contrast use is prohibited in patients with advanced kidney disease, who also carry high surgical risks of cardiopulmonary bypass. Transesophageal echocardiography-guided catheter intervention with zero contrast use is presented in this report, along with technical details about planning the procedure. Covered stent exclusion of SVD without contrast use has not been reported in the literature so far.